A aptidão física relacionada à saúde: uma análise do perfil de escolares de uma escola básica do município de Ananindeua-PA - BRITO, Walber Martins (2020)
The present study emerges from a research whose general objective is to investigate the level of physical fitness related to health (AFRS) of schoolchildren of a basic school in the city of Ananindeua-PA, with the following specific objectives: to compare the components of physical fitness related to health among the sexes and to identify the prevalence of schoolchildren who meet the critical health values established by PROESP - Br, for physical fitness related to health. It was a research developed in the qualitative-quantitative, correlational, transverse and descriptive approach. The sample consisted of schoolchildren of both sexes, aged between 11 and 16 years of age from a State school in the municipality of Ananindeua - PA, of which 30 were female. Anthropometric, strength, endurance and flexibility tests were performed based on the PROESP-Br instrument. The statistical treatment used in the present study was composed of the descriptive analysis of the data. These data were submitted to analysis of variance (ANOVA) and the means of the treatments were compared by the complementary test of means of Turkey to 5%, using the program Statistica 7.0. For all statistical procedures a value of (p≤0.05) was adopted. The results made it possible to conclude that: in the 14-year age group, boys present a significant difference (p ≤ 0.05) higher in the general resistance variable than girls; abdominal strength / resistance in the 14-year age range, being higher in males and BMI in the age range of 12 and 13 years, with females at both ages being higher than males. Regarding the critical health values of BMI, healthy zone: all boys and 83% of girls and zone of risk: 16% of girls; general resistance, healthy zone: 33% of both sexes and zone of risk: 66% of both sexes; flexibility, healthy zone: all boys and 66% of girls and zone of risk: 33% of girls and general strength / resistance, all are in the zone of risk. With the results found, it is important to perform physical activity to improve levels of physical fitness related to the health of schoolchildren. Therefore, intervention programs are suggested that aim at the health and quality of life of these students, also pointing out the importance of Physical Education classes in relation to the increase in their level of physical activity.